Factors Associated to Choice of Birth Attendance in Work Area Of Silago Health Center, Dharmasraya Regency In 2017 - Lailathul Husna; Abdiana Abdiana; Sunesni Sunesni (Universitas Andalas, 2017)
Maternal mortality in Indonesia can occur during pregnancy, labor and delivery. The biggest cause is bleeding. Bleeding can occur during labor or postpartum. Birth attendant can be an indirect determinant of the incidence in postpartum hemorrhage. The aim of this study is to determine factors associated to choice of birth attendance.An analitycal research based cross sectional study was conducted from November 2016-November 2017. The study included 66 subjects who gave birth in 2016 were selected by purposive sampling technique. Data were collected by questionnaire. The collected data were analyze with chi square test using p value <0,05The result of statistic test showed that there was a significant correlation between knowledge (p = 0,000) and attitude (p=001) with the choice of birth attendant. There was no significant correlation between age (p = 0,253), education (p=0,071), employment (p=0,227) and accesibility (p=p=1,000) with the choice of birth attendant. Meanwhile, for support of the husband level chi square test was not performed.From the results of the study it can be concluded that knowledge and attitude were factors related to choice of birth attendance. Meanwhile, age, education, employment and accesibility were not factors associated to choice of birth attendance in work area of Silago Health Center.